PERAN PENDIDIKAN NON FORMAL DALAM MENINGKATKAN PEMAHAMAN KEAGAMAAN UMAT - Imam Amanu; Kukuh Santoso; Dian Mohammad Hakim (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
The spread of non-formal education in the community to involve the role of the community encourages researchers to conduct research with the aim of identifying the roles, strategies and outcomes of non-formal education in increasing religious understanding of the community at Trimulya village, Mukok sub-district, West Kalimantan. This type of research is using qualitative research with the type of case study. The results of the research are: 1) The role of the non-formal educational institutions of the Jaami'atus Salam Mosque, that is, as promoters of formal education, as social change for people, social control of the community and forum for the growing ukhuwah. 2) The strategy pursued by non-formal education institutions is one of them through doctrine. 3) One of the results of non-formal education carried out is the growing awareness of people about prayer in congregation.Kata Kunci: Pendidikan non formal, pemahaman keagamaan, masjid Jaami’atus